Level of Preparedness of BEED Graduating Students on their Student Practice Teaching During A.Y. 2021-2022: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The BEED graduating students are the trainees that take Bachelor in Elementary Education at Bestlink College of the Philippines. The BEED Graduating Students are now facing the new learning styles/mode because of the COVID-19 pandemic. Also, the preparedness of BEED graduating students today for their practice teaching has been affected due to the COVID-19 pandemic that is facing the world today. Practice teaching is a period a student teacher spends teaching at a school as part of their training. Many resources they can use in teaching are limited and not accessible. It is important if the BEED graduating students in the Bestlink College of the Philippines acknowledge or acquire the preparedness to practice teaching. However, the Pandemic is not a hindrance to the Graduating BEED students because of the virtual teaching of some professors in their school, so the learning of strategies in teaching is continuous, and some of the strategies that they learn during this time of pandemic. However, this COVID-19 pandemic is one of the problems facing Graduating BEED students since this crisis limits the experiences that BEED students need to practice teaching in a real classroom. The experiences and different strategies that their professor can teach through online classes are not insufficient or inadequate for students to be prepared for their practice teaching.